The Absorptive Capacity of Operational Budget and Monetary Policy Fiscal Cost - صالح مظهر محمد (Journal of Economics and Administrative Sciences, 2012)
In light of the enquiry raised by the Economist Mary Finn in 1995 concluding that high utilization in absorptive capacity of the economy is of inflationary tendency for industrial countries due to the equality between high rates of utilization of absorptive capacity and resource – shortage conditions leading to price inflation, the same idea was used to prove that budget utilization of operational costs and elevating absorptive capacity at the expense of investment budget leads to inflationary tendency that becomes a burden on financing the step- in policy of the Central bank to control prices through its foreign currency reserves at a time when the economy turned into an importer of non- tradable goods and being subject to Balassa-Samuelson effect based on intensifying non- traded goods price increase in industrial countries in coordination with its growth acceleration to be exported to Iraq as an inflationary force increasing the level of economic imbalances depleting the foreign currency needs of the Central Bank through the increase in the cost of financial or monetary step –in policy which is considered a disease of high consumption societies living on rental resources receiving as a result, price shocks from industrial countries due to the transition towards importing non- tradable goods to become tradable goods.